A seated image of Lakulisa on the Latatabimba (lintel) of the Shrine - Temples of India Project Team (Jio Institute, 2024)
Seen here is a seated image of Lakulisa on the latatabimba (lintel) of the shrine along the western boundary of the Mahanaleshwar temple complex. The deity is holding a lakut (staff) in his hand. Lakulisa is a form of Shiva central to the Pashupata tradition of Shaivism.